Intraoperative Diagnosis of Gallbladder Volvulus - Hassan Mohamed Ali; Eyad Rabih Abdul Wahab; Amjad Damaj; Bassam Moussawi; Walid Audi; Mohammad Haidar; Youssef Badra (Case Reports in Surgery)
Background. A gallbladder torsion typically presents as an acute abdomen presentation with nonspecific clinical signs. When not detected by a clinician preoperatively, it can lead to the delay of emergency surgery and possible misdiagnosis for other, more common causes of an acute abdomen. Case Presentation. We report the case of acute gallbladder volvulus in an 80-year-old woman complaining of constant pain in the right upper quadrant of the abdomen. Conclusions. The patient was successfully treated with cholecystectomy. The case highlights the high index of suspicion required to diagnose the condition preoperatively in this population of patients to reduce complications such as biliary peritonitis and death.